Análise de eficiência energética de um sistema de abastecimento de água de uma indústria cimenteira - Amaral, Cassandra Naiff do (2013)
The Brazil is a developing nation, where economic growth is directly proportional to the consumption of the various energy sources. Thus, the trend is that demand for energy will become greater than the supply, generating a great concern about the possible lack of energy. Given this reality, government policies direct efforts to diversify the country's energy matrix. However, generate more power is not enough: there is a need, in addition to the diversification of energy sources, save on use and eliminate waste. Within this context, the industrial sector is considered the highest energy consumption, where the main source is electricity consumed. In the specific case of the cement industry, electricity accounts for the second largest source of consumption and its use is practically all for the driving force, which in turn, has a high potential for energy efficiency. Thus, in order to analyze the energy performance of a cement industry by eliminating the waste of electricity, studies have been conducted and identified points of improvements in water supply system of a cement factory with a capacity of 10 million bags of cement per year. As part of the research and energy efficiency solutions, has deployed a new automation project, which provided the achievement of improvements in the operation, control, supervision and system measurements and their electrical parameters. These improvements were made possible due to the development and application of logical control for the level of general water tank and deployment of new technologies and to control the drive of centrifugal pumps. Results showed that the activation of the centrifugal pumps through frequency inverters is more efficient than the direct drive type match and / or soft-start. How to control the level of the general reservoir, it was evident that the Control type Proportional, Integral and Derivative maintains the level of the general constant reservoir and pump operation in continuous, without increasing power consumption. Thus, it has become the most suitable for achieving energy efficiency in the factory Water Supply System